Potential for Incompatibility, Instability, and Prescription Drug Interactions in Pulveres Prescription Pediatric Patients at RSI (Islamic Hospital) Sultan Hadlirin, Jepara, Indonesia - Setyoningsih, Heni; Gendis Purno Yudanti; Rakhmi Hidayati; Sri Fitriyaningsih (Open Access Indonesian Journal of Medical Reviews, 2023)
In Indonesia, there are still many doctors who prescribe compounded medicines for pediatrics, including pulveres. Compounding is an alternative for pediatrics who cannot swallow tablets, but compounding medicines is a concern because it can cause incompatibility and instability during storage and cause side effects. drug interactions. This study aimed to determine the potential for incompatibility, instability, and drug interactions on pediatric patient prescription sheets. This research is descriptive observational, and data collection is carried outretrospective, data taken from prescription sheets for pediatric patients at RSI Sultan Hadlirin Jepara. The total sample in this study was 247 prescriptions that met the inclusion criteria. The results of the study showed that the age classification of patients 0-5 years who received pulveres prescriptions was 175 (71.8%), while for those aged 6-11 years, it was 72 (29.1%). %). Based on the number of medications, 197 (80.1%) patients received 4-6 medications, while 50 (20.3%) pediatric patients received 2-3 medications. There is no potential for 0% incompatibility. There is the potential for instability in the pediatric prescription sheets. As many as 62 (25.1%) of the active drug substance preparations that experience instability include CTM, paracetamol, and vitamin B complex. There were 126 (51.0%) potential drug interactions based on the pharmacodynamic mechanism of action and 126 (51.0%) based on moderate severity in the salbutamol tablet preparation with pseudoephedrine. It can be concluded that on the prescription sheet, there is no potential for 0% incompatibility, there is a potential for instability of 62 (25.1%), and there is moderate interaction, and pharmacodynamic mechanisms were 126 (51.0%).